THE STUDY OF OSCILLATIONS IN THE QUASI-REGULATED THREE-SPAN BEAMS ON ELASTIC SUPPORTS - Zhelezniak, H. S.; Soldatov, K. I.; Zhelezniak, R. S. (Science and Transport Progress, 2007)
In work on the example of three-flight irregular beam on resilient supports influence of the once-personal on inflexibility resilient supports is probed on a regular beam, and influence of different stiffness of resilient supports (identical between itself) is similarly probed on a beam, irregular on lengths of flights. It is shown that at the certain parameters of irregularity in practical calculations it is possible to utilize simple solutions for the regular systems, got close dependences, graphs